Perancangan Mesin Sealer Box Guna Menunjang Proses Produksi dan Mengurangi Kelelahan Kerja di Perusahaan Percetakan - Alifiah Wulan Syafira; Hery Murnawan (Jurnal Serambi Engineering, 2024)
This company is an industry that operates in the field of printing boxes made of paper such as duplex, ivory, art paper, mirror coated, HVS and the like. This company uses a make-to-order system or what is known as a production strategy where the company makes products based on customer orders. The production process of this company starts from printing, finishing, laminating, gluing, packing and sorting. The problem in this company is in the gluing section, especially when the packing is done manually and in a bent position, which can cause fatigue if done for a long period of time and can lead to certain muscle disorders or musculoskeletal disorders (MSDs). Therefore, the researcher proposes to design a tool that can support the production of gluing, especially the packaging part, by designing a carton sealing tool so that the packaging process can be speeded up and the level of fatigue caused by an uncomfortable working position can be reduced. This research uses data collection methods by means of interviews and observations of workers' complaints of discomfort, so that the results are complaints of fatigue, namely in the shoulders, back and waist. Based on the results of these observations, it is necessary to design tools to make them more comfortable and increase production output.